1990
DOI: 10.1620/tjem.162.269
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular filtration response to acute loading with protein from different sources in healthy volunteers and diabetic patients.

Abstract: To evaluate the effects of acute protein loading on the glomerular filtration rate, albumin excretion rate and concentration of plasma amino acids, ten healthy volunteers and six type 2 diabetic patients with normoalbuminuria were studied before and after eating 0.7 g/kg body weight of tuna fish, boiled egg white, cheese or tofu (bean curd) on separate days. Furthermore, to study the possible role of glucagon, growth hormone, atrial natriuretic peptide and kallikrein in the responses of glomerular filtration r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…In contrast, ingestion of egg white or bean curd did not produce increased plasma levels of these amino acids or glomerular hyperfiltration (35,36). In previous studies in healthy volunteers and diabetic patients, the plasma levels of alanine, glycine, and arginine increased significantly only after ingestion of tuna fish, which caused a significant increase in GFR.…”
Section: Conclusion-restricted Di-mentioning
confidence: 74%
“…In contrast, ingestion of egg white or bean curd did not produce increased plasma levels of these amino acids or glomerular hyperfiltration (35,36). In previous studies in healthy volunteers and diabetic patients, the plasma levels of alanine, glycine, and arginine increased significantly only after ingestion of tuna fish, which caused a significant increase in GFR.…”
Section: Conclusion-restricted Di-mentioning
confidence: 74%
“…Previous studies that have reported raised plasma ANP concentrations involved more heterogeneous populations than ours, 14,18 patients recruited having either Type 2 or Type 1 DM, with or without hypertension, varying degrees of renal dysfunction, and with concomitant use of various medication. 27,28 We chose to study newly diagnosed patients with Type 2 DM with no complications of diabetes, who were normotensive, normoalbuminuric, and on no current medication. By selecting this group of patients some of the confounding variables of other studies have been avoided.…”
Section: Discussionmentioning
confidence: 99%
“…Nakamura et al (14) found, in acute feeding studies, that individuals with type 1 or type 2 diabetes and microalbuminuria did not have a significant change in GFR during 3 h after eating tuna fish or bean curd (tofu). In nondiabetic individuals and individuals with diabetes and normoalbuminuria, there was a significant increase in GFR after tuna fish but not after tofu (12). In a study lasting 4 weeks using normoalbuminuric subjects with type 1 diabetes, Kontessis et al (13) found that GFR, RPF, and median urinary albumin excretion were significantly lower with PP compared with AP diets.…”
Section: Outcome Parametersmentioning
confidence: 97%
“…More problematic is the effectiveness of reducing the amount of dietary protein to at least 0.8 -1.0 g ⅐ kg body wt Ϫ1 ⅐ day Ϫ1 (11) or changing the type of protein. Studies performed in normoalbuminuric individuals with diabetes have suggested that changing the composition of the diet by altering the source of protein from animal to plant, either acutely in the setting of a standard test meal (12) or for up to 4 weeks (13), might produce beneficial renal effects. However, in another acute study, individuals with type 1 or type 2 diabetes and microalbuminuria showed no significant change in renal function when given plant-based protein (PP) versus animal-based protein (AP) (14).…”
mentioning
confidence: 99%